Evaluasi Pelaksanaan Senam Ibu Hamil Di Kelas Ibu Hamil - Luh Ersi Tunggal Putri; Ni Made Karlina Sumiari Tangkas; Putu Sukma Megaputri; putu dian prima kusuma dewi (2022)
Exercise for pregnant women in the class for pregnant women is one of the health programs that is expected to play a role in reducing maternal morbidity and mortality. This study aims to evaluate the implementation of exercise for pregnant women in the class of pregnant women in Sambangan Village, the working area of ​​the Sukasada I Health Center. This research methode used a qualitative type of research conducted with in-depth interviews, observation and document review. The informants in this study were 10 people including the Head of the Puskesmas, the KIA Program Holder, the person in charge of the pregnancy exercise program, the facilitator and six pregnant women. The results of the study indicate that the input aspects of HR planning, infrastructure facilities, targets, and their allocation have been well structured and carried out according to the guidelines. In the aspect of the process of implementing pregnancy exercise, it has been carried out according to a predetermined schedule. In the output aspect, it is known that the average attendance of pregnant women in each activity is 80%, a monitoring and evaluation process has been carried out with the results and has not involved the health office in the monitoring process, the monitoring results are reported in the form of a quarterly activity report. In the short-term outcome aspect, this pregnancy exercise provides benefits for increasing physical and mental health for pregnant women. In the aspect of medium-term outcome, the percentage of normal deliveries and the presentation of disorders or complications experienced by pregnant women and childbirth were found to be below the national data. In the aspect of long-term outcomes in the last 5 years, there were no cases of maternal death in Sambangn Village, Sukasada I Health Center Working Area.